Comparative Analysis of Academic, Behavioral, and Psychophysiological Variables in Male and Female Vocational Training Students - Vicente Javier Clemente-Suárez; Ana Isabel Beltrán-Velasco; Daniel Mendoza-Castejón; Stephanie Rodríguez-Besteiro; Francisco López-Varas; Alexandra Martín-Rodríguez (MDPI AG, 2024)
Background/Objectives: The purpose of this study was to investigate whether or not there are notable differences between male and female vocational training students in terms of academic, behavioral, and psychophysiological characteristics. Methods: A total of 411 vocational training students, 210 of whom were male and 201 of whom were female, participated in an online survey that assessed academic, behavioral, and psychophysiological patterns. Results: In terms of extraversion and openness to experience, our research revealed that no statistically significant differences were noticed. When it came to agreeableness, however, significant differences were seen, with female students getting higher marks than male students. Furthermore, we found that there were significant gender differences in terms of neuroticism and conscientiousness, with female students achieving higher scores than male students. When compared to their male counterparts, females displayed higher performance in terms of academic success. They also demonstrated superior values in terms of reported stress, anxiety, and cognitive inflexibility. Conclusions: The findings of this study provide a more in-depth understanding of the numerous factors that have an impact on students engaging in vocational training. This will serve as a foundation for the development of individualized instructional and support programs.